Letter (copy) : Basque Children's Fund - Tewson, Vincent
029-0090-001 A/AEN/VAB. HVT/FC/72. Secretary's. 25th November, 1937. Mr. A. G. Newman, The Co-operative Wholesale Society Ltd., 99, Leman Street, E.1. Dear Mr. Newman, Basque Children's Fund Very many thanks for your letter of the 23rd November from which I note that the grant of £5 has been exceeded by an amount of 9/3d. I would suggest that the grant might be extended to cover the account in question. In order to save your time I would further suggest that in the event of your being in agreement with this proposal it is not necessary for you to acknowledge this letter. Yours sincerely, Assistant Secretary. 292/946/29/90